The Effect of Acupuncture and Si Ni San Herb on GERD Patient - Saidi, Viedya Novalinda; Amalia, Anindini Winda; Setiawan, Jessi Suryani; Sulaiman, Yandy (Jurnal Kesehatan Holistic, 2023)
Background: Gastroesophageal Reflux Disease (GERD) is a disorder in which gastric contents reflux repeatedly into the esophagus causing symptoms and/or complications that interfere with quality of life. Existing western medicine has not been able to provide maximum treatment. Objective: To determine the benefits of acupuncture and Chinese herbal combinations in treating GERD. Methods: This quasy-experimental study used a two-group pre-post test design. The subjects of research were 26 respondents who had been grouped by two groups namely the Acupuncture group (13 people) and the Acupuncture and Herbal group (13 people) according to inclusion and exclusion criteria. The acupuncture group was given acupuncture at points ST 36 Zusanli, CV 12 Zhongwan, PC 6 Neiguan for 1 month twice a week. In the acupuncture and herbal groups, acupuncture was given as in the acupuncture group and added herbal Si ni san twice a day @3 gr for a month. Results: In the acupuncture and herbal groups the use of acupuncture points ST 36 Zusanli, CV 12 Zhongwan, PC 6 Neiguan and Si Ni San for 1 month was more effective in reducing GERDQ score by 6.08 with p value 0,001. Conclusion: The use of acupuncture and Si Ni San is more effective than acupuncture alone in lowering GERDQ score and reducing symptoms in patients with GERD